2020
DOI: 10.1088/2053-1591/ab6e32
|View full text |Cite
|
Sign up to set email alerts
|

In situ decomposition of Ti2AlN promoted interfacial bonding in ZnAl-Ti2AlN biocomposites for bone repair

Abstract: In this study, in situ decomposition of Ti 2 AlN was used to obtain strong interfacial bonding in Zn7Al-Ti 2 AlN composites prepared via laser melting. During the preparation process, the Al atoms in Ti 2 AlN could diffuse out of the lattice due to the weak bonding between Al and Ti, followed by easily diffusing into the liquid Zn7Al matrix. Consequently, the diffused Al could bond with the Al in Zn7Al matrix owing to their inherent chemical affinity, leading to a strong interfacial bonding in Zn7Al-Ti 2 AlN c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Therefore, the tensile strength increased from 203 of ZA27 to 310 MPa of ZA27-Ti 3 AlC 2 biocermets, and the bending strength of ZA27-Ti 3 AlC 2 biocermets increased by 55% than Ti 3 AlC 2 . Similarly, our recently study reported Zn-based biocermet with strong interface bonding ascribed to the in situ reaction between the Zn alloys and Ti 2 AlN [167]. Qia et al [168] fabricated Ti 3 SiC 2 and TiC reinforced Al 2 O 3 -based cermets by the in situ reaction between ceramics reinforcement and Ti matrix.…”
Section: In Situ Reactionsupporting
confidence: 60%
“…Therefore, the tensile strength increased from 203 of ZA27 to 310 MPa of ZA27-Ti 3 AlC 2 biocermets, and the bending strength of ZA27-Ti 3 AlC 2 biocermets increased by 55% than Ti 3 AlC 2 . Similarly, our recently study reported Zn-based biocermet with strong interface bonding ascribed to the in situ reaction between the Zn alloys and Ti 2 AlN [167]. Qia et al [168] fabricated Ti 3 SiC 2 and TiC reinforced Al 2 O 3 -based cermets by the in situ reaction between ceramics reinforcement and Ti matrix.…”
Section: In Situ Reactionsupporting
confidence: 60%
“…In this matter, using the selective laser melting technique, a study found that this process resulted in diffusion of the Al atoms in Ti 2 AlN out of the lattice so that the Al atoms could bond with the matrix forming Zn 7 Al. 99 Also, due to atom diffusion, Ti atoms separated from the Ti 2 AlN. The resulting Zn 7 Al-Ti 2 AlN composite had besides the main Zn enrich phase, Al enrich phase, and Ti 2 AlN phase, two new phases of TiN and Al 0.64 Ti 0.36 which were present at the interface and contributed to improved load transfer.…”
Section: General Overviewmentioning
confidence: 99%
“…The resulting Zn 7 Al-Ti 2 AlN composite had besides the main Zn enrich phase, Al enrich phase, and Ti 2 AlN phase, two new phases of TiN and Al 0.64 Ti 0.36 which were present at the interface and contributed to improved load transfer. 99 A disadvantage of in-situ processing of MMCs is that dispersed materials are limited to only those that are thermodynamically stable in a particular matrix. Also, the size and shape of particles are determined by the kinetics of the process during the nucleation and growth activities.…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation